Distinct Inter-Joint Coordination during Fast Alternate Keystrokes in Pianists with Superior Skill - Furuya, Shinichi; Goda, Tatsushi; Katayose, Haruhiro; Miwa, Hiroyoshi; Nagata, Noriko (Frontiers in Human Neuroscience, 2011)
Musical performance requires motor skills to coordinate the movements of multiple joints in the hand and arm over a wide range of tempi. However, it is unclear whether the coordination of movement across joints would differ for musicians with different skill levels and how inter-joint coordination would vary in relation to music tempo. The present study addresses these issues by examining the kinematics and muscular activity of the hand and arm movements of professional and amateur pianists who strike two keys alternately with the thumb and little finger at various tempi. The professionals produced a smaller flexion velocity at the thumb and little finger and greater elbow pronation and supination velocity than did the amateurs. The experts also showed smaller extension angles at the metacarpo-phalangeal joint of the index and middle fingers, which were not being used to strike the keys. Furthermore, muscular activity in the extrinsic finger muscles was smaller for the experts than for the amateurs. These findings indicate that pianists with superior skill reduce the finger muscle load during keystrokes by taking advantage of differences in proximal joint motion and hand postural configuration. With an increase in tempo, the experts showed larger and smaller increases in elbow velocity and finger muscle co-activation, respectively, compared to the amateurs, highlighting skill-level-dependent differences in movement strategies for tempo adjustment. Finally, when striking as fast as possible, individual differences in the striking tempo among players were explained by their elbow velocities but not by their digit velocities. These findings suggest that pianists who are capable of faster keystrokes benefit more from proximal joint motion than do pianists who are not capable of faster keystrokes. The distinct movement strategy for tempo adjustment in pianists with superior skill would therefore ensure a wider range of musical expression.